Preparation and characterization of nano-SiO2/paraffin/PE wax composite shell microcapsules containing TDI for self-healing of cementitious materials. (20th January 2020) - Du, Wei; Yu, Jianying; He, Bianyang; He, Yanheng; He, Peng; Li, Ying; Liu, Quantao
Highlights: Nano-SiO2 /paraffin/PE wax microcapsules containing TDI were prepared. The mechanical property of microcapsules is improved by adding nano-SiO2 in shell. Crack of mortars with nano-SiO2 /paraffin/PE wax microcapsules was self-healed in 4 h. Abstract: Cement concrete materials are prone to form internal micro-cracks during service, which can be self-healed via microcapsule method. In this paper, self-healing microcapsules were prepared through melt condensation method with nano-SiO2 /paraffin/PE wax composite shell and toluene-di-isocyanate (TDI) healing agent. The core fraction and compactness of microcapsules were measured. Particle size distributions, morphologies, micromechanical properties and chemical structure of microcapsules were characterized by laser particle size analyzer, scanning electron microscopy (SEM), nanoindentation test and Fourier transform infrared spectroscopy (FTIR), respectively. Self-healing capability of mortars containing microcapsules was investigated. The results depicted that core fraction of nano-SiO2 /paraffin/PE wax composite shell microcapsule was 72.6%, and the size of the microcapsules was mainly between 400 and 600 µm. Since nano-SiO2 was added to the shell material, the elastic modulus and hardness of the microcapsule reached 1.87 GPA and 61.67 MPa respectively, and the weight loss rate decreased by only 2.6% within 60 d. SEM showed that nano-SiO2 /paraffin/PE wax composite shell microcapsules were regular spherical with rough surface, and the shell thickness was about 1/20 of the diameter. The result of FTIR indicated that TDI was encapsulated into the nano-SiO2 /paraffin/PE wax composite shell successfully. The compressive strength recovery rate of the mortar containing nano-SiO2 /paraffin/PE wax composite shell microcapsules was 87.8% after 60% fc0 pre-load for 10 d self-healing in air. Moreover, the nano-SiO2 /paraffin/PE wax composite shell microcapsule could completely self-heal the surface crack of mortar with a maximum width of 0.48 mm within 4 h, which showed that it had good self-healing capability for cracks in cementitious materials.